Postapplication Advisement for U.S. Medical School Reapplicants: One School's Program - Ballejos, Marlene P; Schmitt, Cheryl L; McKinney, Kara L; Sapien, Robert (Academic medicine, 2019)
Reapplicants make up over one-quarter of U.S. medical school applicants. Postapplication advisement (PAA) can provide potential reapplicants with concrete strategies for improvement, a contextualized basis for their scores, and a realistic idea of their chances for success. However, more data showing the effectiveness of PAA and an analysis of best practices are needed for PAA programs to be more widely adopted. In 2010, the University of New Mexico School of Medicine (UNM SOM) created a PAA program that involves a postapplication seminar (PAS), mandatory self-assessment and action plan development, and an individual consult with an admissions dean to prepare participants for reapplication. From 2010 to 2016, 892 applicants who interviewed and were rejected at UNM SOM were eligible to participate in PAA. Of these, 478 (53.6%) chose to participate in PAA over the seven-year period. Males had a higher participation rate (246/430; 57.2%) compared with females (232/461; 50.3%; P = .04). African Americans had a higher participation rate (12/17; 70.6%) and American Indian/Alaska Natives had a lower participation rate (17/64; 26.6%) than any other race/ethnicity. Of reapplicants who were subsequently accepted, 140/178 (78.7%) attended PAS and a consult, and 7/178 (3.9%) attended PAS only, compared with 31/178 (17.4%) of subsequently accepted reapplicants who did not participate in any PAA (P < .001). Additional research should focus on the best approach for assisting reapplicants with prioritizing areas for improvement in their application. Demographic data may be used to target outreach to specific populations.